2022
DOI: 10.3389/fpls.2021.769700
|View full text |Cite
|
Sign up to set email alerts
|

Improved 93-11 Genome and Time-Course Transcriptome Expand Resources for Rice Genomics

Abstract: In 2002, the first crop genome was published using the rice cultivar 93-11, which is the progenitor of the first super-hybrid rice. The genome sequence has served as a reference genome for the indica cultivars, but the assembly has not been updated. In this study, we update the 93-11 genome assembly to a gap-less sequence using ultra-depth single molecule real-time (SMRT) reads, Hi-C sequencing, reference-guided, and gap-closing approach. The differences in the genome collinearity and gene content between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In addition, our IMY genome assembly scored a Merqury quality value (QV) of 31.42 and a Merqury k-mer completeness of 96.89. Since a recent publication reported that an improved genome assembly of the indica variety 93-11, which is a well-known high-quality genome assembly, scored a QV of 31.55 (Wang et al 2022), our assembly was of sufficient quality as a high-quality genome assembly.…”
Section: Overview Of the Imy Genome Assemblymentioning
confidence: 77%
“…In addition, our IMY genome assembly scored a Merqury quality value (QV) of 31.42 and a Merqury k-mer completeness of 96.89. Since a recent publication reported that an improved genome assembly of the indica variety 93-11, which is a well-known high-quality genome assembly, scored a QV of 31.55 (Wang et al 2022), our assembly was of sufficient quality as a high-quality genome assembly.…”
Section: Overview Of the Imy Genome Assemblymentioning
confidence: 77%
“…The quality of the transcriptome annotation could help with fast and accurate estimation of transcript expression and AS events using the RNA-seq data with the help of the 3DRNA-seq tool ( Chaudhary and Kalkal, 2021 ; Guo et al, 2021 ; Vitoriano et al, 2021 ; Escudero-Martinez et al, 2022 ). Despite rice being an important crop plant and several attempts being made in the past to improve its transcriptome annotation and AS diversity, IndicaRTD contains a significantly higher number of transcript isoforms ( Lu et al, 2010 ; Zhang et al, 2010 ; Zhang H. et al, 2019 ; Schaarschmidt et al, 2020 ; Wang S. et al, 2022 ; Hasan et al, 2022 ; He et al, 2022 ). Several single gene studies have identified the role of AS transcript isoforms in the eukaryotic system including the plant system specifically in rice ( Ganie and Reddy, 2021 ; Singh and Ahi, 2022 ; Wright et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alternative splicing (AS) emerged as one of the key regulatory mechanisms in the eukaryotic system ( Wang S. et al, 2022 ; Wright et al, 2022 ). AS plays a significant role in the development and response to biotic and abiotic stressors in plants and therefore provides key revenue to exploit and increase rice production ( Calixto et al, 2018 ; Filichkin et al, 2018 ; James et al, 2018 ; Laloum et al, 2018 ; Zhang G. et al, 2019 ; Dantas et al, 2019 ; Qin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…National indica rice sequencing data from RiceVarMap database (Zhao et al 2015 ), variations of 3024 3KRG accession from SNP-seek database (Locedie et al 2017 ) and variations of 998 wild rice lines from our recently research (Zhang et al 2022 ) that used to conduct population structure and phylogenetic analysis in this study were subjected to the same data processing pipeline. A recently released and refined indica 9311 reference genome was also used to check the results of population structure analysis (Wang et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%